Analisis Besi (Fe) dalam Air Sumur di Daerah Kergan, Sukoharjo secara Spektrofotometri Serapan Atom - Elina Hartono; Dyah Susilowati; Sarastriningsih Sarastriningsih (Jurnal Farmasi Indonesia, 2010)
Well water is a vital water source for Indonesian inhabitant especially at rural area. Well water is made by digging the ground manually with difference depth according to the kind of land and the site of water source i.e. about 5-20 meters or more. The experiment was aimed to find out whether there was iron in well water and the content of iron at Kergan – Sukoharjo. The method used to find out iron content was Atomic Absorption Spectrophotometer. Preparation of sample was done by wet destruction method because the sample was already in liquid form. Analysis could be done by putting the obtained sample absorbance into linier regression equation using standard curve until the content was obtained. The result of the experiment showed that all samples of well at Kergan – Sukoharjo that analyzed qualitatively contained iron. The iron content in sample A = (0.3751 ± 0.0416) ppm; sample B = (1.0437 ± 0.0119) ppm, and sample C = (1.4845 ± 0.0830) ppm. The iron content in sample A fulfilled the requirement of Indonesian National Standard 01 – 0220 – 1987, while sample B and C were more than the requirement of Indonesian National Standard 01 – 0220 – 1987.